Криптоанализ на основе атак по побочным каналам - Олейников, Р. В.; Минаков, А. Г. (ХНУРЭ, 2011)
This work describes the state situation in the area of side-channel attacks. It describes the various side channel known cryptanalysis methods available from the public literature. These attacks pose a serious threat to the security of cryptographic modules in the specific model with physical access o the attacking devic. In consequence, cryptographic implementations have to be evaluated for their resistivity against such attacks and the incorporation of different countermeasures has to be considered.
Keywords: криптографический алгоритм; криптографический протокол